OpenGeoSys tutorial : computational hydrology II: groundwater quality modeling /: computational hydrology II: groundwater quality modeling. (2017) - Sachse, Agnes; Nixdorf, Erik; Jang, Eunseon; Rink, Karsten; Fischer, Thomas; Xi, Beidou; Beyer, Christof; Bauer, Sebastian; Walther, Marc; Sun, Yuanyuan; Song, Yonghui
No abstract available